2019
DOI: 10.3390/met9121344
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Functionally Graded Materials to Differentiate the Effects of Surface Severe Plastic Deformation, Roughness and Chemical Composition on Cell Proliferation

Abstract: Additive manufacturing allows the manufacture of parts made of functionally graded materials (FGM) with a chemical gradient. This research work underlines that the use of FGM makes it possible to study mechanical, microstructural or biological characteristics while minimizing the number of required samples. The application of severe plastic deformation (SPD) by surface mechanical attrition treatment (SMAT) on FGM brings new insights on a major question in this field: which is the most important parameter betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…As reported in previous studies, a certain degree of roughness not only improves the cell affinity but also increases the contact area with the wound and thereby accelerates the haemostatic process. [31][32][33] Therefore, change in the morphology of CS as well as its improved biocompatibility may be due to the modication of Arg and AuNPs.…”
Section: Semmentioning
confidence: 99%
“…As reported in previous studies, a certain degree of roughness not only improves the cell affinity but also increases the contact area with the wound and thereby accelerates the haemostatic process. [31][32][33] Therefore, change in the morphology of CS as well as its improved biocompatibility may be due to the modication of Arg and AuNPs.…”
Section: Semmentioning
confidence: 99%
“…Thirteen research papers have been published in this Special Issue of Metals. The papers cover a wide spectrum of topics, including (i) deformation mechanisms, the mechanical properties and fatigue behaviour of SPD-processed materials [1][2][3][4][5][6][7], (ii) microstructural and mechanical stability at elevated temperatures [8,9], phase formations in alloys [10], the improvement of physical properties (electrical conductivity [11], magneto-resistance [12]) and biomedical properties (biocorrosion resistance [6], biocompatibility [13]) by SPD.…”
Section: Contributionsmentioning
confidence: 99%
“…It is shown that the magnitude of the granular magnetoresistance can be tuned by changing the HPT process parameters. In [13], the effect of SMAT was compared for two binary functionally graded materials (Ti-Nb and Ti6Al4V-Mo) to study the effect of chemistry, roughness and SPD microstructure on mesenchymal stem cell adhesion and proliferation. The increased roughness introduced by SMAT improved the cellular adhesion, but did not influence their proliferation capability.…”
Section: Contributionsmentioning
confidence: 99%
“…At the very top, there are lump-shaped grains that are rich in Nb and Mo. The grains in the sample exhibit epitaxial growth as a result of the layer-by-layer deposition process [66]. The experimental findings indicated that the desired chemical composition in the construction wall can be precisely attained by modifying the proportion of iron and aluminum wire feed.…”
mentioning
confidence: 95%
“…The mechanical properties of the deposited wall have been measured, and the specimens have exhibited room temperature strength and ductility values that are comparable to those observed in prior studies. Given the importance of corrosion resistance in the application of this material, future research will concentrate on understanding the corrosion mechanism of the Fe-FeAl FGM [66]. Most recently, the deposition methods were advanced to enhance the properties of the FGM parts by hybrid additive manufacturing (HAM).…”
mentioning
confidence: 99%